Аналіз процесу організації руху вантажопотоків в ланцюгах постачання - Шраменко, Наталя; Шраменко, Владислав (ТзОВ «Галицька видавнича спілка», 2021)
The reasons of low efficiency of the organization of transportations of cargoes from suppliers to consumers are defined. The directions of optimization of the movement of cargo flows at the organization of transportations from suppliers to consumers on the basis of logistic principles are offered.
Analysis of the movement organizing process of freight flows in supply chains
Keywords: 656.025